Underweight increases the risk of early death in tuberculosis patients. Issue 12 (28th November 2017) - Yen, Yung-Feng; Tung, Fu-I; Ho, Bo-Lung; Lai, Yun-Ju
Abstract: Evidence regarding the association between BMI and mortality in tuberculosis (TB) patients is limited and inconsistent. We investigated the impact of BMI on TB-specific and non-TB-specific mortality with respect to different timing of death. All Taiwanese adults with TB in Taipei were included in a retrospective cohort study in 2012–2014. Multinomial Cox proportional hazards regression was used to evaluate the associations between BMI, cause-specific mortality and timing of death. Of 2410 eligible patients, 86·0 % (2061) were successfully treated, and TB-specific and non-TB-specific mortality occurred for 2·2 % (54) and 13·9 % (335), respectively. After controlling for potential confounders, underweight was significantly associated with a higher risk of all-cause mortality (adjusted hazard ratio (AHR) 1·57; 95 % CI 1·26, 1·95), whereas overweight was not. When cause-specific death was considered, underweight was associated with an increased risk of either TB-specific (AHR 1·85; 95 % CI 1·03, 3·33) or non-TB-specific death (AHR 1·52; 95 % CI 1·19, 1·95) during treatment. With joint consideration of cause-specific and timing of death, underweight only significantly increased the risk of TB-specific (AHR 2·23; 95 % CI 1·09, 4·59) and non-TB-specific mortality (AHR 1·81; 95 % CI 1·29, 2·55) within the first 8 weeks of treatment. This study suggests that underweight increases the risk of early death in TB patients during treatment.